PENGARUH SELF EFFICACY DAN LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN PT. SINAR NIAGA SEJAHTERA - Alparindi, Amanda; Arianto, Tezar (UM. Bengkulu, 2025)
Human resources must be managed properly to increase effectiveness and efficiency in the organization, for this reason it is necessary to have good human resource management to support the achievement of organizational goals. The purpose of this study is to analyze whether self-efficacy and locus of control simultaneously have a significant effect on employee performance at PT Sinar Niaga Sejahtera. This type of research is a descriptive quantitative approach. The population in this study were 55 employees. The data collection techniques in this study were observation and questionnaires. The data analysis techniques used are multiple linear regression, the coefficient of determination, and hypothesis testing. It was found that Self Efficacy has a significant effect on employee performance at PT. Sinar Niaga Sejahtera Locus Of Control has a significant effect on employee performance at PT Sinar Niaga Sejahtera, Self Efficacy (X1) and Locus Of Control (X2) together have a significant effect on employee performance (Y) at PT. Sinar Niaga Sejahtera. Based on the correlation coefficient test, the value of R = 0.952 and the coefficient of determination = 0.906 means that Self Efficacy (X1) and Locus Of Control (X2) contribute an influence of 0.906 or 58.1% to Employee Performance (Y) at PT. Sinar Niaga Sejahtera while the remaining 0.419 or 41.9% is influenced by other variables that are not included in this research. Keywords: Self efficacy, Locus of control, Employee Performance